Adding insult to brain injury: young adults' experiences of residing in nursing homes following acquired brain injury. Issue 1 (2nd January 2019) - Dwyer, Aoife; Heary, Caroline; Ward, Marcia; MacNeela, Pádraig
Abstract: Purpose: There is general consensus that adults under age 65 with acquired brain injury residing in nursing homes is inappropriate, however there is a limited evidence base on the issue. Previous research has relied heavily on third-party informants and qualitative studies have been of questionable methodological quality, with no known study adopting a phenomenological approach. This study explored the lived experiences of young adults with brain injury residing in aged care facilities. Methods: Interpretative phenomenological analysis was employed to collect and analyze data from six semi-structured interviews with participants regarding their experiences of living in nursing homes. Results: Two themes were identified, including "Corporeal prison of acquired brain injury: broken selves" and "Existential prison of the nursing home: stagnated lives". Results illustrated that young adults with acquired brain injury can experience aged care as an existential prison in which their lives feel at a standstill. This experience was characterized by feelings of not belonging in a terminal environment, confinement, disempowerment, emptiness and hope for greater autonomy through rehabilitation. Conclusion: It is hoped that this study will provide relevant professionals, services and policy-makers with insight into the challenges and needs of young adults with brain injury facing these circumstances. Implications for rehabilitation: This study supports the contention that more home-like and age-appropriate residential rehabilitation services for young adults with acquired brain injury are needed. As development of alternative accommodation is a lengthy process, the study findings suggest that the interim implementation of rehabilitative care in nursing homes should be considered. Taken together with existing research, it is proposed that nursing home staff may require training to deliver evidence-based rehabilitative interventions to those with brain injury. The present findings add support to the call for systemic change in Ireland, to clarify the acquired brain injury care pathway and establish integrated rehabilitation services.